2008
DOI: 10.1007/s00248-007-9356-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotic Therapy on Human Fecal Microbiota and the Relation to the Development of Clostridium difficile

Abstract: The gastrointestinal (GI) tract is a complex ecosystem. Recent studies have shown that the human fecal microbiota is composed of a consortium of microorganism. It is known that antibiotic treatment alters the microbiota, facilitating the proliferation of opportunists that may occupy ecological niches previously unavailable to them. It is therefore important to characterize resident microbiota to evaluate its latent ability to permit the development of pathogens such as Clostridium difficile. Using samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 28 publications
3
67
0
3
Order By: Relevance
“…A significant body of research has demonstrated that disturbances in this balance can disrupt intestinal homeostasis. Multiple disease states may arise, at least in part, in response to altered indigenous microbial communities in the gut (10,47,53,55). Conversely, research on probiotics indicates that the normal balance between the indigenous microbiota and the host can be protected or restored through the administration of beneficial microbes (6,45,59).…”
mentioning
confidence: 99%
“…A significant body of research has demonstrated that disturbances in this balance can disrupt intestinal homeostasis. Multiple disease states may arise, at least in part, in response to altered indigenous microbial communities in the gut (10,47,53,55). Conversely, research on probiotics indicates that the normal balance between the indigenous microbiota and the host can be protected or restored through the administration of beneficial microbes (6,45,59).…”
mentioning
confidence: 99%
“…Indeed, recent work highlighted that microbiota composition, assessed before antibiotic treatment, differed between individuals who developed CDI as a consequence and those who did not (7). Chang et al showed a decreased fecal microbiota diversity in adults with recurrent CDI (4).…”
mentioning
confidence: 99%
“…An entropathogenic bacterium Salmonella enterica inhibits the growth of microbiota in the gut and subsequently predisposes mice to colitis development [44]. Alteration of the gut microbiome by antibiotics in humnas can lead to the development of pathogenic Clostridium difficile infection [45]. In germ free mice, invariant natural killer T (iNKT) cells in lamina propria contribute to inflammatory bowel disease and asthma.…”
Section: Intestinal Homeostasis and Immune Responsesmentioning
confidence: 99%